Faktor-Faktor yang Berhubungan dengan Manajemen Kebersihan Mestruasi Remaja pada Masa Pandemi COVID-19 - Aning Subiyatin; Nuryaningsih Nuryaningsih; Fatimah Fatimah; Putri Malika Prastiari (FORIKES, 2023)
Adolescence is a period of transition from children to adulthood, which is marked by menstruation and requires special attention. It is important to practice menstrual hygiene management to prevent reproductive tract infections and other complications. This study aimed to find out how menstrual hygiene management practices and related factors, during the COVID-19 pandemic. The design used in this study was cross-sectional. The sample size was 156 respondents. The dependent variable in this study was menstrual hygiene management practices; while the independent variables were the characteristics of female students, the characteristics of parents of female students, knowledge of menstruation, experience of menstruation and sources of information. Data collection was carried out by interviews and questionnaires. Data analysis was performed by Chi-square test. The results of the analysis showed that most menstrual hygiene management practices were in the good category (55.1%), the majority of female students' knowledge was good (51.9%). The p-value for each factor was knowledge = 0.215, father's education = 0.149, mother's education = 0.009. It was concluded that the practice of managing menstrual hygiene at SMPN 232 had been going well and was related to the mother's education.Keywords: menstruation; menstrual hygiene management; teenager; mother's education ABSTRAK Masa remaja merupakan masa peralihan dari anak-anak menuju dewasa, yang ditandai dengan menstruasi dan memerlukan perhatian khusus. Manajemen kebersihan menstruasi penting untuk dipraktikkan guna mencegah infeksi saluran reproduksi dan komplikasi lainnya. Penelitian ini bertujuan untuk mengetahui bagaimana praktik manajemen kebersihan menstruasi dan faktor yang berhubungan, pada masa pandemi COVID-19. Desain yang digunakan dalam penelitian ini yaitu cross-sectional. Ukuran sampel adalah 156 responden. Variabel dependen dalam penelitian ini adalah praktik manajemen kebersihan menstruasi; sedangkan variabel independen adalah karakteristik siswi, karakteristik orang tua siswi, pengetahuan menstruasi, pengalaman menstruasi dan sumber informasi. Pengumpulan data dilakukan dengan wawancara dan kuisoner. Analisis data dilakukan dengan uji Chi-square. Hasil analisis menunjukkan bahwa praktik manajemen kebersihan menstruasi yang terbanyak adalah dalam kategori baik (55,1%), mayoritas pengetahuan siswi perempuan adalah baik (51,9%). Nilai p untuk masing-masing faktor adalah pengetahuan = 0,215, pendidikan ayah = 0,149 pendidikan ibu = 0,009. Disimpulkan bahwa praktik manajemen kebersihan menstruasi di SMPN 232 berjalan dengan baik dan berhubungan dengan pendidikan ibu. Kata kunci: menstruasi; manajemen kebersihan menstruasi; remaja; pendidikan ibu